Solve for m m/(m-9)-10=9/(m-9)

Math
mm-9-10=9m-9
Find the LCD of the terms in the equation.
Tap for more steps…
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
m-9,1,m-9
The LCM is the smallest positive number that all of the numbers divide into evenly.
1. List the prime factors of each number.
2. Multiply each factor the greatest number of times it occurs in either number.
The number 1 is not a prime number because it only has one positive factor, which is itself.
Not prime
The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.
1
The factor for m-9 is m-9 itself.
(m-9)=m-9
(m-9) occurs 1 time.
The LCM of m-9,m-9 is the result of multiplying all factors the greatest number of times they occur in either term.
m-9
m-9
Multiply each term by m-9 and simplify.
Tap for more steps…
Multiply each term in mm-9-10=9m-9 by m-9 in order to remove all the denominators from the equation.
mm-9⋅(m-9)-10⋅(m-9)=9m-9⋅(m-9)
Simplify mm-9⋅(m-9)-10⋅(m-9).
Tap for more steps…
Simplify each term.
Tap for more steps…
Cancel the common factor of m-9.
Tap for more steps…
Cancel the common factor.
mm-9⋅(m-9)-10⋅(m-9)=9m-9⋅(m-9)
Rewrite the expression.
m-10⋅(m-9)=9m-9⋅(m-9)
m-10⋅(m-9)=9m-9⋅(m-9)
Apply the distributive property.
m-10m-10⋅-9=9m-9⋅(m-9)
Multiply -10 by -9.
m-10m+90=9m-9⋅(m-9)
m-10m+90=9m-9⋅(m-9)
Subtract 10m from m.
-9m+90=9m-9⋅(m-9)
-9m+90=9m-9⋅(m-9)
Cancel the common factor of m-9.
Tap for more steps…
Cancel the common factor.
-9m+90=9m-9⋅(m-9)
Rewrite the expression.
-9m+90=9
-9m+90=9
-9m+90=9
Solve the equation.
Tap for more steps…
Move all terms not containing m to the right side of the equation.
Tap for more steps…
Subtract 90 from both sides of the equation.
-9m=9-90
Subtract 90 from 9.
-9m=-81
-9m=-81
Divide each term by -9 and simplify.
Tap for more steps…
Divide each term in -9m=-81 by -9.
-9m-9=-81-9
Cancel the common factor of -9.
Tap for more steps…
Cancel the common factor.
-9m-9=-81-9
Divide m by 1.
m=-81-9
m=-81-9
Divide -81 by -9.
m=9
m=9
m=9
Exclude the solutions that do not make mm-9-10=9m-9 true.
No solution
Solve for m m/(m-9)-10=9/(m-9)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top